4CPS-219 Analysis of patients' information needs attending an outpatient pharmaceutical care unit: pilot test. (2nd March 2018) - Andreu, M; Maso, N El Hilali; Modamio, P; Aguas, M; Pons, M; Mariño, E
Abstract : Background: We are in a context where patients should become the centre of the healthcare system and where information is increasingly diverse and easily accessible. Adapting the information to the patients' characteristics and to their point of view is essential for their empowerment. However, there is a significant variability between diseases in the research and elaboration of validated methods to evaluate, quantify and compare information needs. Purpose: The aim of this study was to carry out a pilot test to validate a questionnaire that analyses the information needed by patients who visited the Outpatient Pharmaceutical Care Unit (OPCU) of a hospital. Second, to obtain a tool that indicates which information they want to receive and what they do not, and from which sources of information. Material and methods: The internationally validated EORTC QLQ-INFO25 questionnaire for oncology patients was used. In order to be used in different pathologies, changes according to validity, viability and reliability criteria were made. Results: To assess validity, an expert committee suggested appropriate changes to ensure that items were representative of the new target population. As a result, the modified EORTC QLQ-INFO25 was produced, being suitable for piloting (n=30). Viability was assessed by conducting the questionnaire. It was considered a necessary simplification, by eliminating items and modifying statements. Many patients raised doubts that had not been raised previously and were solved. Furthermore, Cronbach's alpha statistical analysis indicated that reliability was high, as well as the items that could be eliminated if needed. Conclusion: The definitive validation study questionnaire (n=200) was therefore obtained through relevant modifications based on observational criteria (viability) and statistics (reliability). It consists of 1–15 common items and 16–17 specific for neurology or rheumatology. Two sections were added: 'Variables of interest' and 'Preferred sources of information'. According to the answers, patients prefer to be informed by specialists, followed by the rest of health professionals. They are satisfied with the quantity, quality and usefulness of the information received. However, they would like to receive more information about treatment and improvement in their quality of life. References and/or Acknowledgements: Thanks to the whole hospital team for their willingness and especially to the patients for their collaboration No conflict of interest